An Evaluation of Current Preventative Measures Used in Equine Practice to Maintain Distal Forelimb Functionality: A Mini Review - Clarke, Emily J.; Gillen, Alex; Turlo, Agnieszka; Peffers, Mandy J. (Frontiers in Veterinary Science, 2021)
Horses are used in a variety of equestrian disciplines predisposing them to musculoskeletal injury or disease including osteoarthritis and tendinopathy. As a result, a number of preventative measures are used within equine medicine and husbandry, ranging from therapeutic shoeing to the use of nutraceuticals. Despite their popularity and routine use evidence base and clinical outcomes are variable, bringing into question the efficacy of these prophylactic measures. In recent years a small number of studies have been performed examining the effect of specific strategies in order to quantify the preventative and protective claims such modalities have on joint and forelimb health. Few have robustly demonstrated a capacity to protect the limb by reducing inflammation, or promoting regenerative pathways. This review focusses on performance horses specifically, and the resounding theme that emerges in current research is the need for longitudinal studies to inform scientific conclusions surrounding single and multi-modal use. Furthermore, there is a requirement to prioritise evidence-based medicine to inform optimal clinical practice.